Addressing family planning needs among low-literate population in peri-urban areas of Delhi, India: a qualitative inquiry - Atre, Sachin R.; Kudale, Abhay M.; Howard, Heather M. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Since several decades, population control has remained one of the major challenges for India. Understanding family planning (FP) related knowledge and practices, especially among low-literate population groups is important for increasing the reach of FP services nearer to them, which is an essential step for population control as well as to prevent unwanted pregnancies. Methods: We conducted a cross-sectional, qualitative research study among low literate population in peri-urban areas of New Delhi, bordered with Uttar Pradesh (U.P.) state. We selected and interviewed 27 participants including married men and women in the age range 18-34 years using semi-structured interview schedules. The focus of inquiry was on fertility awareness; beliefs and practices related to menstruation, pregnancy and FP methods etc. and decision making about FP. The data were processed for thematic analysis. Results: The study revealed lack of basic scientific knowledge about fertility in this community which often resulted into unwanted pregnancies. This finding has major implications especially when the Government’s FP program is geared mainly towards sterilization and conventional spacing methods. The study further confirmed that traditional beliefs and practices like separating women during menstruation still prevail in many joint families, but less likely in the nuclear ones. There were mixed opinions about spacing methods. Husband was reported to be main decision maker in FP process in this male dominated society. Regarding sources of information on FP, women reported elder women, lady clinicians and peers whereas men reported only peers. Conclusions: This study points out various barriers for FP around which basic FP education for both men and women in this community need to be provided. The study will have implications for other parts of India which share the same socio-cultural milieu as this community.